Pengaruh Quality of Work Life, Beban Kerja dan Stres Kerja terhadap Person Organization Fit serta Implikasinya pada Kinerja Pegawai di UPT Puskesmas Sepaku III Kabupaten Penajam Paser Utara Tahun 2024 - Setyaji, Setyaji; Sidqi, Abdul Gani; Nugroho, Taufan; Asnar, Etty Sofia Mariati; Paramarta, Vip (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
The numerous programs implemented by Puskesmas, both activities inside and outside the building, which include promotive, preventive, curative, and rehabilitative aspects, require alignment between individuals and the organization to enhance performance and improve the quality of Puskesmas services. This study aims to analyze the effect of quality of work life, workload, and work stress on person-organization fit and its implications for employee performance at UPT Puskesmas Sepaku III, Penajam Paser Utara Regency. The subjects of this research include all employees at Puskesmas Sepaku III, Penajam Paser Utara Regency, with a sample size of 50 individuals. Data analysis was performed using Partial Least Square (PLS) analysis techniques. The results show that employees at Puskesmas Sepaku III have a good quality of work life, a moderate workload, moderate work stress, a high person-organization fit, and high performance. Quality of work life and workload significantly affect person-organization fit, while work stress does not have an effect on person-organization fit. Overall, quality of work life, workload, and work stress significantly influence employee performance, both directly and through the mediation of person-organization fit. A good quality of work life, low workload, and low work stress, supported by a good person-organization fit, will enhance employee performance at UPT Puskesmas Sepaku III, Penajam Paser Utara Regency.